Epidemiological aspects of caries complications (Эндодонтия Today)
The retrospective analysis of 1000 out-patient cards of patients of 35-44 years which have addressed in clinic Chita SMА in 2012 is carried out. Analyzed affections anatomic groups of teeth (incisors and canines, premolars, molars) both jaws on segments, and also structure nosological forms and their communication among themselves. It is revealed high affections able-bodied population by a pulpitis and apical a periodontitis. A chronic periodontitis (the fibrous form) bottom molars were prevailing. At the analysis of communications it is not revealed authentic correlation in face-to-face group, direct dependence between frequency of a pulpitis and a periodontitis in group molars is revealed strongly. Authors explain the elicited facts distinctions in morphology of endodonts, possible accumulation of microorganisms (passive sedimentation) and their faster penetration on system of root channels bottom molars owing to gravity.